2022
DOI: 10.3390/su14042379
|View full text |Cite
|
Sign up to set email alerts
|

Saudi Non-Oil Exports before and after COVID-19: Historical Impacts of Determinants and Scenario Analysis

Abstract: The diversification of the economy including its exports is at the core of Saudi Vision 2030. The vision targets to raise non-oil export from 16% to 50% of non-oil GDP by 2030. Achieving this, in addition to other goals, necessitates a better understanding of the non-oil export relationship with its determinants. However, we are not aware of a study that estimates the impacts of the determinants on Saudi non-oil exports covering the recent years of reforms and low oil prices and that conducts simulations for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 133 publications
2
10
0
4
Order By: Relevance
“…Raid et al (2024) investigated the impact of non-oil institutional sectors on the economic growth of Saudi Arabia from 1970 to 2020 by employing Vector Auto-Regressive (VAR) and variance decomposition and they found that the growth of the oil sector is highly susceptible to shocks and negatively affecting the economic growth while the growth of non-oil sector had more stability and reduces the adverse shocks on GDP. Similarly, Hasanov et al (2022) examined the role of non-oil exports on the economy of Saudi Arabia by using the co-integration technique over the time frame 1983-2018. The findings of their study supported the concept of export-led growth while they didn't find any evidence of the Dutch disease.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Raid et al (2024) investigated the impact of non-oil institutional sectors on the economic growth of Saudi Arabia from 1970 to 2020 by employing Vector Auto-Regressive (VAR) and variance decomposition and they found that the growth of the oil sector is highly susceptible to shocks and negatively affecting the economic growth while the growth of non-oil sector had more stability and reduces the adverse shocks on GDP. Similarly, Hasanov et al (2022) examined the role of non-oil exports on the economy of Saudi Arabia by using the co-integration technique over the time frame 1983-2018. The findings of their study supported the concept of export-led growth while they didn't find any evidence of the Dutch disease.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been acknowledged for a long time that exports are a leading driver for sustainable economic growth (environmental and social sustainability to a certain level) by boosting the rate of employment, encouraging investment particularly, foreign direct investment, and advanced technologies, producing positive externalities for other sectors. Nonetheless, all these factors are pivotal for sustainable inclusive economic development as they can contribute to the augmentation of economic activity, a rise in the level of income, and poverty alleviation (Hasanov et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows how dependent the country is on the commodity. In 2019, the oil industry made up 41% of the GDP, 77% of the money came from exports, and 64% went into the government's budget (Hasanov et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Although most of Saudi Arabia's non-oil exports are tied to oil production, such as chemicals and plastics, the country's non-oil exports have grown by a factor of seven, or 12.5% a year, between 2002 and 2019. This means that the oil business still accounts for a large share of Saudi Arabia's GDP, even though the non-oil sector has developed rapidly in recent years (Hasanov et al, 2022).…”
Section: Introductionmentioning
confidence: 99%